Clinical Profile of Stroke Chameleons Receiving Intravenous Thrombolysis: Insights from a Single-Center Experience - Alejandro M. Brunser; Pablo M. Lavados; Paula Muñoz-Venturelli; Verónica V. Olavarría; Eloy Mansilla; Gabriel Cavada; Maria Elena Trejo; Pablo E. González (Cerebrovascular Diseases Extra)
Introduction: In emergency rooms (ERs), 5% of patients experiencing an acute ischemic stroke (AIS) receive an alternative diagnosis; these cases are known as stroke chameleons (SC). The percentage of SC treated with intravenous thrombolysis (IVT) and the characteristics have not been well described. We aimed at investigating the variables associated with the probability receiving IVT. Methods: In this prospective study, we included consecutive patients with SC admitted at the ER of Clínica Alemana between September 2014 and October 2023. Results: Among 1,193 stroke patients; sixty-three (5.2%) corresponded to SC. Ten of these cases (15.8%, 95% CI: 8.8–26.8) were treated with IVT, mean door-to-needle (DTN) time of 85.7 (SD 35) min, median of 73.5 (IQR 62–113) min. SCs who underwent IVT were younger (p = 0.01), with higher NIHSS (p = 0.05). They presented more frequently with altered level of consciousness in the NIHSS (p = 0.01), language abnormities (p = 0.001), and dysarthria (p = 0.01). In multivariate analysis, none of the variables were significantly associated with IVT. A secondary analysis showed that only time to brain imaging was significantly associated with IVT (OR: 0.99; 95% CI: 0.98–0.99; p = 0.01). Conclusions: Almost 1 out of every 7 SC could be treated with IVT but with a prolonged DTN time; the chance of being treated is associated with time to brain imaging. Introduction: In emergency rooms (ERs), 5% of patients experiencing an acute ischemic stroke (AIS) receive an alternative diagnosis; these cases are known as stroke chameleons (SC). The percentage of SC treated with intravenous thrombolysis (IVT) and the characteristics have not been well described. We aimed at investigating the variables associated with the probability receiving IVT. Methods: In this prospective study, we included consecutive patients with SC admitted at the ER of Clínica Alemana between September 2014 and October 2023. Results: Among 1,193 stroke patients; sixty-three (5.2%) corresponded to SC. Ten of these cases (15.8%, 95% CI: 8.8–26.8) were treated with IVT, mean door-to-needle (DTN) time of 85.7 (SD 35) min, median of 73.5 (IQR 62–113) min. SCs who underwent IVT were younger (p = 0.01), with higher NIHSS (p = 0.05). They presented more frequently with altered level of consciousness in the NIHSS (p = 0.01), language abnormities (p = 0.001), and dysarthria (p = 0.01). In multivariate analysis, none of the variables were significantly associated with IVT. A secondary analysis showed that only time to brain imaging was significantly associated with IVT (OR: 0.99; 95% CI: 0.98–0.99; p = 0.01). Conclusions: Almost 1 out of every 7 SC could be treated with IVT but with a prolonged DTN time; the chance of being treated is associated with time to brain imaging. Introduction: In emergency rooms (ERs), 5% of patients experiencing an acute ischemic stroke (AIS) receive an alternative diagnosis; these cases are known as stroke chameleons (SC). The percentage of SC treated with intravenous thrombolysis (IVT) and the characteristics have not been well described. We aimed at investigating the variables associated with the probability receiving IVT. Methods: In this prospective study, we included consecutive patients with SC admitted at the ER of Clínica Alemana between September 2014 and October 2023. Results: Among 1,193 stroke patients; sixty-three (5.2%) corresponded to SC. Ten of these cases (15.8%, 95% CI: 8.8–26.8) were treated with IVT, mean door-to-needle (DTN) time of 85.7 (SD 35) min, median of 73.5 (IQR 62–113) min. SCs who underwent IVT were younger (p = 0.01), with higher NIHSS (p = 0.05). They presented more frequently with altered level of consciousness in the NIHSS (p = 0.01), language abnormities (p = 0.001), and dysarthria (p = 0.01). In multivariate analysis, none of the variables were significantly associated with IVT. A secondary analysis showed that only time to brain imaging was significantly associated with IVT (OR: 0.99; 95% CI: 0.98–0.99; p = 0.01). Conclusions: Almost 1 out of every 7 SC could be treated with IVT but with a prolonged DTN time; the chance of being treated is associated with time to brain imaging. Introduction: In emergency rooms (ERs), 5% of patients experiencing an acute ischemic stroke (AIS) receive an alternative diagnosis; these cases are known as stroke chameleons (SC). The percentage of SC treated with intravenous thrombolysis (IVT) and the characteristics have not been well described. We aimed at investigating the variables associated with the probability receiving IVT. Methods: In this prospective study, we included consecutive patients with SC admitted at the ER of Clínica Alemana between September 2014 and October 2023. Results: Among 1,193 stroke patients; sixty-three (5.2%) corresponded to SC. Ten of these cases (15.8%, 95% CI: 8.8–26.8) were treated with IVT, mean door-to-needle (DTN) time of 85.7 (SD 35) min, median of 73.5 (IQR 62–113) min. SCs who underwent IVT were younger (p = 0.01), with higher NIHSS (p = 0.05). They presented more frequently with altered level of consciousness in the NIHSS (p = 0.01), language abnormities (p = 0.001), and dysarthria (p = 0.01). In multivariate analysis, none of the variables were significantly associated with IVT. A secondary analysis showed that only time to brain imaging was significantly associated with IVT (OR: 0.99; 95% CI: 0.98–0.99; p = 0.01). Conclusions: Almost 1 out of every 7 SC could be treated with IVT but with a prolonged DTN time; the chance of being treated is associated with time to brain imaging.